Anomalous nonequilibrium phonon scattering in the Weyl semimetal WP_{2} - Junhong Yu; Jianzhou Zhao; Yangyang Lv; Yadong Han; Zhang Hang; Jinlong Xu; Jianbo Hu (Physical Review Research, 2023)
The type-II Weyl semimetal (WSM) β-WP_{2} was recently demonstrated as a supreme quantum material with various interestingtransport properties. Toward deciphering these peculiar transport phenomena for future topological device applications, it is highly necessary to understand the dynamical process of phonon scatterings under nonequilibrium conditions. By performing temperature-dependent coherent phonon spectroscopy in β-WP_{2}, we provide here direct experimental evidence that phonons decaying into electron-hole pairs overwhelm the anharmonic phonon-phonon scattering process. Remarkably, the dominating phonon-electron coupling in β-WP_{2} is further supported by observations of the transient Fano resonance. First-principles calculations suggest that the anomalous phonon decaying results from the acoustic bunching and the limited phonon density of states in β-WP_{2}. Our real-time observations provide dynamical insight into quasiparticle scatterings that are of vital importance for fundamental transport properties in β-WP_{2}.